ETHICS AND SPORTS (ETHICS BY KVIRIN VASILJ, 1917-2005) (Fiep Bulletin - online, 2014)
With the affirmation of professional sports in the past century as well as the rise of a voluminous entertainment industry related to it, sport ethics has come to be not only a fertile terrain for testing and developing philosophical notions and theories, but also a foremost point of contact between philosophy, civil institutions, and the society at large. In this article we discuss about ethics and sport. Ethical principles we perceive like that do Kvirin Vasilj (1917-2005), Croatian philosopher and intellectual. Those ethical principles we applied to the sport. Intention to make a link between termini as ethics and sports are, the most revolve in one’s mind are negative (non-ethics) feedback such as doping, bribes, corruptions and profits motivated with just one goal – triumph and victory. Contemporary sport is permanent under ethics enquiring temptation because of utilitaristic admission. Sport presents risk, like economy interlacing in the name of triumph no matter of the consequences and in the same time resource of politics propaganda on international level.
Keywords: ethics; ethical principles; sport; Kvirin Vasilj